Anti-SARS-CoV-2 Antibody Level among Renal Transplant Recipients: A Case Report from Nepal - Kamal Ranabhat; Bhuvan Saud; Saroj Adhikari; Suraj Bhattarai; Rojan Adhikari; Bhoj Raj Luitel; Mahesh Raj Sigdel (Case Reports in Urology)
Globally, SARS-CoV-2 has caused significant public health burden, mainly in patients with underlying comorbidities including both communicable and noncommunicable diseases. Solid organ transplant recipients under immunesupressive medication are also amongst the high risk group. There is only sparse data on immunity against SARS-CoV-2 infection among renal transplant recipients. In this case report, we present the level of anti-SARS-CoV-2 antibody of three kidney transplant recipients after vaccination against COVID-19 virus. All three cases had received two doses of Oxford-AstraZeneca COVID-19 vaccine AZD1222 (ChAdOx1). Serological analysis showed protective level of circulating antibodies in the blood of all three cases. Although two out of three patients in the study acquired COVID-19 infection after immunization, they recovered with mild clinical course. Hence, we conclude that despite immune-suppressed status of transplant recipients, COVID-19 vaccination could protect them against severe illness.